2008
DOI: 10.1037/a0013176
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive resources, valence, and memory retrieval of emotional events in older adults.

Abstract: In 2 studies with older adults, the authors investigated the effect of executive attention resources on the retrieval of emotional public events. Participants completed a battery of working memory tasks, as a measure of executive attention, and a battery of tasks assessing memory, as well as subjective experiences associated with the retrieval of remote public events. Participants also rated the valence of each public event story. The group-rated valence of the public event stories predicted retrieval and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
60
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 53 publications
9
60
0
Order By: Relevance
“…It has also been observed after different types of encoding: incidental (Kensinger et al, 2005;Mather & Knight, 2005;Thomas, 2006;Yang & Ornstein, 2011) and intentional (Kensinger et al, 2005), and in different types of retrieval task: free recall (Mather & Knight, 2005;Yang & Ornstein, 2011) and recognition (Kensinger, 2008;Kensinger et al, 2005). In addition, EEM was found for different types of stimuli: pictures (Kensinger et al, 2005;Waring & Kensinger, 2009;Yang & Ornstein, 2011), words (Kensinger, 2008;Thomas, 2006), human faces (Denburg et al, 2003; and public events (Kensinger, 2006;Petrican, Moscovitch, & Schimmack, 2008).…”
Section: Emotional Memory Enhancement In Healthy Ageingmentioning
confidence: 89%
“…It has also been observed after different types of encoding: incidental (Kensinger et al, 2005;Mather & Knight, 2005;Thomas, 2006;Yang & Ornstein, 2011) and intentional (Kensinger et al, 2005), and in different types of retrieval task: free recall (Mather & Knight, 2005;Yang & Ornstein, 2011) and recognition (Kensinger, 2008;Kensinger et al, 2005). In addition, EEM was found for different types of stimuli: pictures (Kensinger et al, 2005;Waring & Kensinger, 2009;Yang & Ornstein, 2011), words (Kensinger, 2008;Thomas, 2006), human faces (Denburg et al, 2003; and public events (Kensinger, 2006;Petrican, Moscovitch, & Schimmack, 2008).…”
Section: Emotional Memory Enhancement In Healthy Ageingmentioning
confidence: 89%
“…If PEs do indeed depend on cognitive control (a finding challenged by some studies; see Allard & Isaacowitz, 2008;Petrican, Moscovitch, & Schimmack, 2008), then this poses constraints on the circumstances under which the phenomenon emerges. Increasing cognitive load by introducing a cognitively demanding secondary task during encoding of emotional words (Mather & Knight, 2005) or during a visual attention task with emotional material (Knight et al, 2007) attenuates or even reverses PEs (i.e., negativity bias).…”
Section: Food For Happy Thought: Glucose Protects Age-related Positivmentioning
confidence: 99%
“…Support for this account comes from two sets of behavioural studies. First, studies on the effect of individual differences in executive functions as measured by neuropsychological tasks, on performance in episodic memory or sustained attention tasks, have shown that older adults who perform better on the executive function tasks are also more likely to show positivity effects in the memory and attention tasks (e.g., Isaacowitz et al, 2009;Mather & Knight, 2005;Petrican, Moscovitch, & Schimmack, 2008). Second, positivity effects found when tasks are performed under full attention conditions are nullified or even reversed when performed under divided attention (Knight et al, 2007;Mather & Knight, 2005), suggesting control processes, or attentional resources, disrupted under divided attention are required for the effect to emerge in older adults.…”
mentioning
confidence: 99%